Pengaruh Motivasi Kerja dan Kompensasi Terhadap Kepuasan Kerja Karyawan studi Kasus di PT Bank Rakyat Indonesia Kanca Medan Putri Hijau - Dhita Adriani Rangkuti; Yovie Ernanda (University of Merdeka Malang, 2020)
PT. Bank Rakyat Indonesia, Tbk is a banking company which is a State-Owned Enterprise (BUMN). BRI Kanca Putri Hijau has 14 shaded branch offices including sub-branch offices and cash offices located in several locations in the city of Medan. Job satisfaction felt by some employees is still lacking and even tends to be dissatisfied. It is suspected that the cause is the lack of work motivation and compensation obtained and it can be seen from the high employee turnover. This research was conducted at PT. Bank Rakyat Indonesia Kanca Medan Putri Hijau which is located at Jl Putri Hijau No 2 A Medan. This type of research is quantitative descriptive case study. The data used in this study are primary data with observation data collection techniques, interviews and distributing questionnaires / questionnaires. And another source is secondary data in the form of documentation studies. The population of this study was 228 respondents with a sample of 145 respondents. The data analysis technique uses multiple linear regression analysis formulas and uses classical assumption tests, research hypothesis testing (t test and F test).The result of this research is that work motivation has a positive and significant effect on job satisfaction, compensation has a positive and significant effect on job satisfaction, work motivation and compensation have a positive and significant effect on job satisfaction.